Umur Relatif Batuan Asal Sedimen Olisostrom Formasi Karangsambung, Kebumen, Jawa Tengah - Purna Sulastya Putra; Praptisih Praptisih (Pusat Survei Geologi, 2020)
The Karangsambung Formation in Kebumen, Central Java is olisostrome deposit that composed of floating rock fragments in the claystone matrix. The age of this formation is still debatable, and it is even unclear that the present age was the age of the formation or the age of the source rock of the olisostrome sediment. In this study, the relative age of the source rock of the olisostrome sediment was identified by using foraminifera data. The relative age identification of the olisostrome source rocks are very important as the identification of olisostrome sediment age is very difficult. The relative age of Karangsambung Formation can be assumed younger than the age of the olisostrome source rocks. Result of Karangsambung Formation age identification with regard to the olisostrome concep will have implications to the regional tectonic model of Java.Keywords: Karangsambung Formation, relative age, source rock, foraminifera, olisostrome.